Jalalludin Muhammad Akbar's policy in India 1556-1605 C - Sari Agustina; sumarjono sumarjono; sumarno sumarno; Ahmad Ryan Pratama (JURNAL HISTORICA, 2020)
Jalalludin Muhammad Akbar is the third king of the Mughal Empire. The Mughal empireis an Islamic-style kingdom that flourished in the western Indian region in the 16thcentury. Mughal in Akbar experienced a golden era that runs a policy strategy such as thepolitical, economic, religious and cultural fields. This study aims to (1) examine thebackground of Jalalluddin Muhammad Akbar's government in India in 1556-1605 AD, (2)to examine the role of Jalalludin Muhammad Akbar in applying Mughal governmentpolicy in India, (3) to examine the results achieved Mughal Work in India on the reign ofJalalludin Muhammad Akbar in India. This research uses historical research methods,with four phases of heuristics, criticism, interpretation, and historiography. The policy ofSultan Akbar's rule was seen as the forerunner of the Mughal forces by the unity of theHindustan society under the Mughal alliance. In the political field Sultan Akbar optimizedthe political system of sulh-e-kul with a base of military power. The economy implementsa trading system with a fair tax system in accordance with income. Multiculturalism in theHindustan lands alters Akbar's thoughts on the field of Mughal religion and art, theapplication of Divine Providence is used inter-religious intolerance in India while in thearts there is a cultural acculturation to cultivate Mughal characteristics. The adoption ofAkbar's policies in 1556-1605 AD led to social change in society to balance the systemrunning in India. These changes led to progress and good relations between Mughal andthe people of Hindustan.